Answer:
The correct answer is x = 3 and y = 8
Explanation:
1. First equation
- 5x + 6y = 33
-5x = 33 - 6y
- x = 33/5 - 6y/5 (Dividing by 5 at both sides of the equation)
x = - 33/5 + 6y/5 (Multiplying by - 1 at both sides of the equation)
2. Second equation
- 18x + 4y = -22
- 18 (-33/5 + 6y/5) + 4y = - 22 (Replacing x by the result of the 1st equation)
594/5 - 108y/5 + 4y = - 22
594 - 108y + 20y = -110 (Multiplying by 5 at both sides of the equation)
-88y = -110 - 594
-88y = -704
-y = - 8 (Dividing by 88 at both sides of the equation)
y = 8 (Multiplying by - 1 at both sides of the equation)
3. Replacing y in the first equation for finding x
x = - 33/5 + 6(8)/5
x = - 33/5 + 48/5
x = 15/5
x = 3
4. Proof of x =3 and y = 8
-5x + 6y = 33
-5 (3) + 6 (8) = 33
-15 + 48 = 33
33 = 33
It's proved that x = 3 and y= 8 are correct